In vitro study on anti-amoebic activity of tualang honey against entamoeba histolytica trophozoite - Mintow, Alvieno Situl (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Anti-bacterial properties of Malaysian honeys have been widely studied. However, the anti-amoebic activity of local honeys against Entamoeba histolytica is still not known. This study was conducted to preliminarily evaluate in vitro activity of one local Malaysian honey which is tualang honey on the growth of E. histolytica trophozoites. Anti-amoebic activity of tualang honey was assessed using a broth dilution method and metronidazole as the control. Different concentrations of honey [6.25% - 25% (weight/volume)] and metronidazole were tested against HM-1:1MSS strain E. histolytica trophozoites in the 96-well flat-bottom microtiter plate under anaerobic condition. The growth of trophozoites in each well was evaluated microscopically using inverted microscope. Trophozoites were monitored for motility and rounding-up and the numbers were scored accordingly. MIC was defined as the lowest concentration of honey dilution at which a 1 + score (>90% rounded up, than the control well) was obtained in the majority of the triplicate wells. It was found that concentrations of tualang honey with a 1 + score ranged from 12.5% to 25% (w/v) while concentrations with 2+ to 4+ scores were between 6.25% and 11.25% (w/v). Therefore, the MIC of tualang honey was 12.5% (w/v). This study showed that the local Malaysian tualang honey has an inhibitory effect on E. histolytica trophozoites in vitro. Thus, it can provide a scientific basis for further evaluations on potential use of local honeys against E. histolytica infection as well as studies related to determination of their anti-amoebic properties.